2022
DOI: 10.5530/ijper.56.3.142
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Novel and Highly Sensitive Stability-Indicating Reverse Phase UPLC Method for Quantification of Dabrafenib and its ten Degradation Products

Abstract: Objectives: Dabrafenib is used as an active pharmaceutical ingredient acts as an inhibitor of the associated enzyme B-Raf, which plays a role in the regulation of cell growth. In the current study, we focused on developing a robust, highly sensitive and stabilityindicating RP-UPLC method for estimation of DBR and its degradation products for the very first time. A stress study has been performed to demonstrate the stability-indicating capability of the method. Materials and Methods: Chromatographic separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…[7] In the literature survey, numerous analytical methods have been developed for the quantitative analysis of Dabrafenib (DAB), including high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), fluorescence technique, and electrophoresis. [8][9][10][11][12][13][14][15][16][17][18][19][20] While these methods are effective and sensitive in detecting and quantifying DAB, they are often associated with drawbacks such as high costs and environmental concerns arising from the extensive use of organic solvents. Additionally, these methods may require lengthy analysis times and the expertise of trained professionals to operate analytical instruments effectively.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In the literature survey, numerous analytical methods have been developed for the quantitative analysis of Dabrafenib (DAB), including high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), fluorescence technique, and electrophoresis. [8][9][10][11][12][13][14][15][16][17][18][19][20] While these methods are effective and sensitive in detecting and quantifying DAB, they are often associated with drawbacks such as high costs and environmental concerns arising from the extensive use of organic solvents. Additionally, these methods may require lengthy analysis times and the expertise of trained professionals to operate analytical instruments effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced analytical techniques like reverse phase high performance liquid chromatography (RP-HPLC) coupled with tandem mass spectrometry (MS/MS) and nuclear magnetic resonance (NMR) spectroscopy are applied vastly for the detection and structure elucidation of all kinds of organic impurities [8,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Separation, identification and characterization of DPs of few anticancer drugs using the UPLC-MSMS technique have been reported. [25][26][27][28][29][30][31][32][33][34] Based on the recommendations of ICH guidelines Q3A (R2) and Q3B (R2), identification and characterization of all the DPs or process-related impurities of dabrafenib have been carried out. [35][36] But to date, no study is reported on the degradation and stability of drugs under varied conditions such as hydrolytic, oxidative, thermal and photolytic.…”
Section: Introductionmentioning
confidence: 99%